GLAUKOSPHAERITE FROM CHROMITITES OF THE VOYKAR-SYNYA MASSIF, POLAR URALS – THE FIRST RELIABLE FIND IN RUSSIA - Yu.V. Erokhin; I.V. Pekov; N.V. Vakhrusheva; P.B. Shiryaev; V.O. Yapaskurt; S.N. Britvin (Минералогия)
Glaukosphaerite and mcguinnessite (carbonates of the rosasite-malachite group) are found in chromitites of the Burkhoyla area, which is located in the northern part of the Voykar-Synya ultramafic massif (Polar Urals). The minerals form green and bluish-green films, small crystals and spherulites (up to 0.3 mm) in cavities of weathered chromitites. This is the first reliable find of glaukosphaerite in Russia. The chemical composition of glaukosphaerite is as follows (wt %): 25.14 NiO, 0.44 CoO, 0.89 FeO, 34.45 CuO, 7.90 MgO, 21.65 CO2 (calc.), 8.86 H2O (calc.), total 99.33. The empirical formula calculated based on the cation sum is (Cu0.88Ni0.68Mg0.40Fe0.03Co0.01)2.00(CO3)(OH)2. The parameters of the monoclinic unit cell of glaukosphaerite calculated from the powder X-ray diffraction data are: a = 12.070(3), b = 9.363(2), c = 3.131(1) Å, β = 98.03(2)º, V = 350.3(3) Å3 . The formation of these carbonates is related to supergene alteration of sulfides (pentlandite and bornite) in chromitites.